Penyuluhan dan edukasi penggunaan obat rasional bagi warga korban banjir bandang di Desa Gunggungan Kidul - Fahmi Dimas Abdul Azis; Rasyidin R; Guntur Fajar A; Bimo Rio F (Jurnal Dedikasi Masyarakat, 2020)
Disasters often occur, especially in vulnerable areas such as mountainous areas which can be affected by flash floods. This was experienced by Gunggungan Kidul Village, Pakuniran District, Probolinggi Regency. Flash floods not only cause economic damage but also health damage that can be experienced after the flood. Therefore, affected residents need to provide health care to treat these health problems, such as pain, fever, stomach acid, and bacterial infections. Health workers include doctors, nurses, pharmacists, academic students, and nursing or pharmacy lecturers. Activities were carried out in Gunggungan Kidul Village which was affected by the flash flood disaster, with several stages of activities, namely preparation and observation, socialization, and social service. Some of the activities carried out are health checks, rational medicine education, and the free provision of medicines to patients affected by flash floods. Rational drug education is carried out using an outreach approach that is given directly to patients as activity participants. This personalization reminds us that each patient experiences various complaints and has different characteristics. The implementation of activities runs in an orderly and controlled manner, where all interprofessional institutions work together by their respective duties and functions. Apart from that, community members participate in activities in an orderly manner making it easier to control. Based on the results of the questionnaire, it was found that the residents felt quite satisfied with implementing community service activities for the residents of Gunggungan Kidul Village from the results of rational medicine counseling and education.